Multiple Unemployment Equilibria: Do Transitory Shocks Have Permanent Effects? - Q. Farooq Akram (Norges Bank, 2000)
This paper tests for multiple equilibria in the Norwegian unemployment rate and investigates whether it displays asymmetric response to positive and negative shocks. Linear and nonlinear univariate models are employed to account for the unemployment behaviour over the period 1972-1997. Among these, only a logistic smooth transition autoregressive (LSTAR) model is data consistent. Accordingly, unemployment is a stationary variable that has switched between two stable equilibria during the sample period. It is shown that a large shock, or a sequence of small shocks, can cause a transition from one equilibrium level to another and thereby have a permanent effect on the unemployment rate. Moreover, unemployment recovers faster from a fall, relative to a given equilibrium level, than from a rise.
hdl:11250/2500536
Keywords: E24; C22; C5; E52; 330; NAIRU; STAR model; Markov regime switching model; hysteresis; multiple unemployment equilibria